Holding China together : diversity and national integration in the post-Deng era - Naughton, Barry; Yang, Dali L. (Cambridge University Press, 2004)
Despite predictions of collapse, China has sustained unity and gained international stature since the Tiananmen crisis of 1989. This volume addresses the 'fragmentation/disintegration thesis' and examines the sources and dynamics of China's resilience. Through theoretically informed empirical studies, the authors consider key institutions for political integration and economic governance.